Identifikasi Awal Bakteri pada Juwana Trochus niloticus Linn. dan Tridacna squamosa Linn. Asal Hatchery Pulau Barrang Lompo Makassar - Magdalena Litaay; Risco B. Gobel; As’adi Abdullah; Subair Subair (Universitas Atma Jaya Yogyakarta, 2007)
The research on early identification of bacterial from juveniles top shell (Trochus niloticus L.) and giant clam (Tridacna squamosa Linn.) was conducted at Unhas’s hatchery at Barrang Lompo island during August-October 2006. Bacteriology test was done at Microbiology Laboratory of Biology Department, Math and Science Faculty, Hasanuddin University, Makassar. The quantitative test was done using Most Probable Number (MPN) and Standard Plate Count (SPC) methods. While the qualitative test included bacteria colony observation, macroscopic, microscopic, and biochemical test. Macroscopic observation was done by assessing the form, elevation, color, ridge, and inner structure of bacterial colony. Microscopic observation was conducted by using Gram and spora stain. The result of MPN method shows the average total bacteria for juveniles top shell is 17.5 x 102 cell/ml and for giant clam is 6.65 x 102 cell/ml, while SPC results indicate the average total bacteria for juveniles top shell is 4.8 x 105 cell/ml and for giant clam is 3.0 x 105 cell/ml, respectively. The result of biochemical test identifies 5 genera of bacteria such as Micrococcus, Bacillus, Streptomyces, Escherichia and Enterobacter.